THE EFFECT OF RETURN ON ASSETS, SALES GROWTH AND DIVIDEND POLICY ON STOCK PRICES OF FOOD AND BEVERAGE SUBSECTOR COMPANIES LISTED ON THE IDX IN 2016-2020 - Tanniamaria Virgin Mamentu; Paulina Van Rate; Fitty Valdi Arie (Universitas Sam Ratulangi, 2022)
Currently, investment is one of the most important factors in the economic growth of a country. Purchases and sales in the capital market based on various considerations can cause the effect of rising or falling stock prices. The purpose of this study was to determine the effect of Return On Assets, sales growth and dividend policy on stock prices of food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. The method used in this research is associative with a quantitative approach. The population in this study amounted to 30 companies based on purposive sampling technique, the number of samples used was 14 companies. The analysis technique used is multiple linear regression. The results showed that the Return on Assets, sales growth and dividend policy simultaneously had a significant effect on stock prices. Return On Assets, sales growth partially has a significant effect on stock prices. Dividend policy partially has a significant effect on stock prices. For investors, the results of this study can be used as a useful consideration for making investment decisions in the capital market. So investors need to pay attention to high Return on Assets, Sales Growth, and Dividend Policy to get high returns, in addition to paying attention to other factors such as macroeconomic conditions in order to obtain optimal capital gains.